2013
DOI: 10.1093/jat/bkt040
|View full text |Cite
|
Sign up to set email alerts
|

Antemortem and Postmortem Methamphetamine Blood Concentrations: Three Case Reports

Abstract: We compare antemortem whole-blood to postmortem peripheral blood concentrations of methamphetamine and its metabolite amphetamine in three medical examiner cases. Antemortem specimens, initially screened positive for methamphetamine by ELISA, were subsequently confirmed, together with the postmortem specimens, by GC-MS analysis following solid-phase extraction. Methamphetamine peripheral blood to antemortem blood ratios averaged 1.51 (± 0.049; n = 3) and amphetamine peripheral blood to antemortem blood ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Considering the methamphetamine data (McIntyre et al 2013c), an experimental (actual) F for methamphetamine of 1.5 is predicted -postmortem peripheral blood concentrations being 1.5 times (on average) greater than the corresponding antemortem concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the methamphetamine data (McIntyre et al 2013c), an experimental (actual) F for methamphetamine of 1.5 is predicted -postmortem peripheral blood concentrations being 1.5 times (on average) greater than the corresponding antemortem concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports elaborating on, and supporting, this model have now been published (McIntyre & Mallett 2012;McIntyre & Meyer Escott 2012;McIntyre & Anderson 2012;McIntyre et al 2013a;McIntyre et al 2013b). Furthermore, a direct correlation between the postmortem peripheral blood and corresponding antemortem concentration -by consideration of the L/P ratio -has been expressed (McIntyre et al 2013c). The report, describing methamphetamine cases, found that the postmortem peripheral blood concentrations were approximately 1.5 times higher than the corresponding concentrations attained in whole blood specimens collected before death.…”
Section: Introductionmentioning
confidence: 99%
“…Human METH users exhibited plasma METH concentrations that ranged from 2 to 3 µM. In comparison, levels can reach 17 µM in individuals arrested for erratic behavior and 87 µM in postmortem samples from non-overdose patients 45,46 . Notably, a marked accumulation of an unchanged concentration of METH has been shown in METH-sensitized rat brain cortex, striatum, and heart, but not in the liver, kidney, or abdominal muscle, following a bolus injection of 4 mg/kg METH, demonstrating a viable reason for the higher toxicity METH use poses to cardiac tissue 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, given recent information documenting the L/P ratio as a marker for PMR, these data support earlier impressions suggestive of potential for benztropine PMR. Based on criteria of L/P ratios exceeding 20–30 L/kg indicative of a propensity for significant PMR and ratios <5 L/kg indicating little to no propensity toward PMR , the L/P ratio in this case of 20.4 L/kg implies significant potential for PMR. On the other hand, based on the earlier C/P ratio model, these numbers suggest, arguably, only a minimal propensity for benztropine PMR, although the possibility of some degree of PMR occurring in the peripheral blood cannot be discounted.…”
Section: Resultsmentioning
confidence: 99%